A multiomics dataset for the study of RNA modifications in human macrophage differentiation and polarisation - Natalia Pinello; Renhua Song; Quintin Lee; Emilie Calonne; Mark Larance; François Fuks; Justin J. -L. Wong (Scientific Data, 2024)
Abstract RNA modifications have emerged as central regulators of gene expression programs. Amongst RNA modifications are N6-methyladenosine (m6A) and RNA 5-hydroxymethylcytosine (5hmC). While m6A is established as a versatile regulator of RNA metabolism, the functions of RNA 5hmC are unclear. Despite some evidence linking RNA modifications to immunity, their implications in gene expression control in macrophage development and functions remain unclear. Here we present a multi-omics dataset capturing different layers of the gene expression programs driving macrophage differentiation and polarisation. We obtained mRNA-Seq, m6A-IP-Seq, 5hmC-IP-Seq, Polyribo-Seq and LC-MS/MS data from monocytes and resting-, pro- and anti-inflammatory-like macrophages. We present technical validation showing high quality and correlation between samples for all datasets, and evidence of biological consistency of modelled macrophages at the transcriptomic, epitranscriptomic, translational and proteomic levels. This multi-omics dataset provides a resource for the study of RNA m6A and 5hmC in the context of macrophage biology and spans the gene expression process from transcripts to proteins.